Bilateral Meningo-Cortical Involvement in Anti-myelin Oligodendrocyte Glycoprotein-IgG Associated Disorders: A Case Report - Ma, Guozhong; He, Jinzhao; Li, Yan; Xu, Yan; Hu, Yunxin; Cui, Fang (Frontiers in Neurology, 2021)
Cortical T2-weighted fluid-attenuated inversion recovery (FLAIR)-hyperintense lesions in anti-myelin oligodendrocyte glycoprotein (MOG)-associated encephalitis with seizures (FLAMES) are mostly unilateral and rarely spread to the bilateral cortex and meninges. We describe a case of MOG-immunoglobulin G (IgG) associated disorder (MOGAD) in a 39-year-old male with bilateral meningo-cortical involvement. The patient was hospitalized for epilepsy, fever, and headache. The initial MRI revealed abnormalities in the sulci of the bilateral frontal, temporal, and parietal lobes. He was considered to have infectious encephalitis and given empiric antibiotic and antiviral therapy, which were ineffective. His condition rapidly improved after the patient was switched to high-dose immunoglobulin therapy. No tests supported the presence of central nervous system (CNS) infections or autoimmune encephalitis. The second and third MRI scans showed reduced but still clearly observable meningo-cortical lesions. The patient was discharged without a definite diagnosis, but reported severe left vision impairment 25 days later. A fourth MRI showed signs typical of demyelinating CNS disease in addition to the original meningo-cortical lesions. The patient's symptoms were initially relieved by low-dose corticosteroid therapy, but they eventually returned, and he was re-admitted. The original lesions were diminished on the fifth MRI scan, but new lesions had developed in the deep white matter. A positive cell-based assay for MOG-IgG in serum confirmed MOGAD. The patient received high-dose corticosteroid treatment followed by an oral methylprednisolone taper, and his visual acuity gradually improved. The sixth and final MRI showed substantial decreases in the original lesions without new lesion formation. This unique case presents the complete diagnosis and treatment process for MOGAD with bilateral meningo-cortical involvement and may provide a reference for prompt diagnosis.